Conceptualizing resilience: An energy services approach. (December 2022) - Tiwari, Shardul; Schelly, Chelsea; Ou, Ge; Sahraei-Ardakani, Mostafa; Chen, Jianli; Jafarishiadeh, Fatemeh
Abstract: Climate change-induced disasters are increasingly affecting communities around the globe. To study the impacts and recovery of the communities from disasters, resilience is increasingly outlined as a useful concept for policymakers and planners. Resilience helps us to understand a system or individual elements of a system on how they can withstand and recover from a disaster. However, the current resilience definition and subsequent frameworks developed based on the definition fail to capture the energy service dimension to understand, measure, and explain resiliency. The capability approach forms the basis of the energy service perspective, outlining that freedom to achieve well-being is of primary human importance. Modern energy, synonymous with electricity today, is a means to derive almost all basic services to develop human capabilities. This deficiency of not looking at resilience from an energy service approach has led to largely ignoring the idea that we need energy services and not only energy to measure and enhance human capabilities during and after a disaster. This paper makes the case that the provisioning of energy services should be centered on understanding and measuring resilience, particularly at a finer resolution of an individual or household level. This paper aims to consider an approach for defining resilience based on the energy services revaluating the development of resiliency frameworks.